Chronology of the western world, 20th century - Society for Visual Education (Chicago, IL The Society, 1985)
Presents a chronicle of the twentieth century. Examines the impact of wars, economic depression, and the atomic bomb on the people of the world.
VHS.
Artists, Richard Erdoes, Libor Pokorny.
Keywords: History, Modern -- 20th century; History, Modern -- 20th century; World history -- 20th century